2001
DOI: 10.1046/j.0028-646x.2001.00272.x
|View full text |Cite
|
Sign up to set email alerts
|

Ozone exposure affects leaf wettability and tree water balance

Abstract: Summary• Relatively little is known about the influences of growing-season background ozone (O 3 ) concentrations on leaf cuticles and foliar water loss.• Using fumigation chambers, leaf wettability and foliar water loss were studied in two poplar species, Populus nigra and P. euramericana , and a conifer, Pseudotsuga menziesii , under three O 3 regimes; control (approx. 1 ppbv O 3 ), urban O 3 exposure (13 -41 ppbv O 3 ), and montane O 3 exposure (30 -45 ppbv O 3 ).• Urban O 3 exposure delayed a decrease in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 42 publications
1
22
0
4
Order By: Relevance
“…1 and 2). At the presence of ozone, the leaves cuticle changes and greater stomatal apertures can lead to increased transpiration (Lee et al, 1990;Turunen and Huttunen, 1990;Schreuder et al, 2001). The AOT40 (accumulated exposure over a threshold of 40 ppb) during the growing season at our study site was 20.12 ppm h, which far exceeded the current critical level for ozone impacts on forest trees of AOT40 5 ppm h (UNECE, 2004).…”
Section: Tablementioning
confidence: 87%
“…1 and 2). At the presence of ozone, the leaves cuticle changes and greater stomatal apertures can lead to increased transpiration (Lee et al, 1990;Turunen and Huttunen, 1990;Schreuder et al, 2001). The AOT40 (accumulated exposure over a threshold of 40 ppb) during the growing season at our study site was 20.12 ppm h, which far exceeded the current critical level for ozone impacts on forest trees of AOT40 5 ppm h (UNECE, 2004).…”
Section: Tablementioning
confidence: 87%
“…The results obtained are consistent with changes in leaves wettability. Schreuder et al (2001) found that increased leaf life span may reduce the hydrophobicity of leaves. Crocford & Richardson (1990) and Sase et al (2008) when performing experiments using both conifer and deciduous species found that older leaves were losing their hydrophobic properties.…”
Section: Discussionmentioning
confidence: 99%
“…Although most studies have standardized the methods by applying a 50‐µl water droplet to the leaf surface (Table ), to our knowledge, no studies have investigated whether the water droplet size influences the water droplet retention measurements. Because Schreuder et al () calculated water droplet retention by applying 10‐µl water droplets, it is uncertain if their water droplet retention measurements are comparable with the other studies in Table , which applied 50‐µl water droplets.…”
Section: Measurement Of Leaf Hydrophobicity and Water Droplet Retentionmentioning
confidence: 99%